Projecting Nation South African Cinemas After 1994. - Moyer-Duncan, Cara (African humanities and the arts., 2020)
"Projecting Nation explores the ways in which national and transnational forces have shaped the representation of race and nation in South African films produced after the transition to a multiracial democracy"--